Optimalisasi Tim UKS tentang Kespro di SMP Pertiwi 1 Kota Jambi - Hesty Hesty; Maimaznah Maimaznah; Muhammad Hidayat (Jurnal Abdimas Kesehatan (JAK), 2026)
Reproductive health (Kespro) is an important aspect that should be introduced from adolescence, as this period is a transition to adulthood marked by physical, psychological, and social changes. A lack of understanding of reproductive health can lead to risky behavior among adolescents. This community service activity was carried out at SMP Pertiwi 1 Kota Jambi with the aim of optimizing the role of the School Health Unit (UKS) in improving students’ knowledge of reproductive health. The method used was health education through counseling, interactive presentations, and group discussions. The activity was conducted from March to August 2025. Evaluation was carried out using pre-test and post-test instruments administered to 10 UKS team students. The results showed that before education, the students’ level of knowledge was in the good category for 8 students (80%), sufficient for 2 students (20%), and poor for 0 students (0%). After education, students’ knowledge improved to the good category for all 10 students (100%), while sufficient and poor categories were not found (0%). Although most students already have good knowledge, there are still 20% of students with sufficient knowledge. Education is needed to align the understanding of all members of the Health and Safety Team, prevent information gaps between students, and ensure all participants have correct and standardized knowledge. These findings indicate a significant improvement in students’ knowledge after receiving education. Thus, this activity proves that reproductive health education through the optimization of the UKS team is effective in increasing knowledge and creating positive changes before and after implementation. It is expected that similar programs can be carried out sustainably so that students gain adequate provisions to maintain reproductive health from an early age.